Dementia care management: going new ways in ambulant dementia care within a GP-based randomized controlled intervention trial. (23rd October 2013) - Eichler, Tilly; Thyrian, Jochen René; Dreier, Adina; Wucherer, Diana; Köhler, Leonore; Fiß, Thomas; Böwing, Georgia; Michalowsky, Bernhard; Hoffmann, Wolfgang
ABSTRACT: Background: Increasing prevalence of dementia is a major challenge for the German healthcare system. The study DelpHi-MV ("Dementia: life- and person-centered help in Mecklenburg-Western Pomerania") aims to implement and evaluate an innovative subsidiary support system for persons with dementia (PwDs) living at home and their caregivers. Methods: DelpHi-MV is a GP-based cluster randomized controlled intervention trial. DelpHi-Intervention aims to provide "optimum care" by integrating multi-professional and multimodal strategies to individualize and optimize treatment of dementia within the framework of the established healthcare and social service system. The intervention is conducted by Dementia Care Managers (DCMs) – nurses with dementia-specific training – at the people's homes. Based on German guidelines for evidence-based diagnoses and treatment of dementia, a comprehensive set of 95 intervention modules – the "DelpHi-Standard" – was defined. Each module consists of predefined trigger condition(s), a subsequent intervention task, as well as at least one criterion for its completion. The intervention begins with a comprehensive assessment of the care situation, needs, and resources. The DCM develops and implements an intervention plan tailored to the individual conditions in close cooperation with the GP. Expected Results and Conclusions: We expect statistically significant differences between control and intervention group in primary outcomes (quality of life, behavioral and psychological symptoms of dementia, pharmacotherapy, caregiver burden). Results can provide evidence for the effectiveness and efficacy of dementia care management according to the "Delphi-Standard" – prerequisites for implementing this concept into routine healthcare.